Effect of Weissella cibaria as probiotic on some on growth factors in Siberian sturgeon Acipenser baerii - Hashemimofrad, M.; Sattari, M.; Khoshkholgh, M.; Shenavar Masuoleh, A.; Abasalizadeh, A. (2016)
The present study was designed to investigate the effect of bacteria Weissella cibaria as to probiotic on growth factors on Siberian sturgeon. The fish averaged 143.55 ± 0.04 g in weight were placed in 12 tanks for 60 days in four treatments everyone to three replicates including 0.2 g probiotic containing 107CFU / g for the first treatment (TA); 2 g probiotic containing 108CFU / g for the second treatment (TB) and 20 mg probiotic containing 109CFU / g for the third treatment (TC), and diet without probiotics for the control treatment (C), respectively and at the end of the trial meantime measurement the growth rate proceed to means Statistical analysis (ANOVA one- way- 95%) although, all probiotics-treated diets were resulted in to increases parameters feed conversation ration (FCR), specific growth rate (SGR) and protein efficiency ratio (PER), body weight index (BWI) comparing to the control group. However, no significant difference Condition Factor (CF) was observed between the treatments and group. Thus using this type of probiotics can be effective in improving the growth parameters.